Electroactive polymer actuated tendon driven micro actuator for robotic application - Billah, Md. Masum; Khan, Md. Raisuddin; Shafie, Amir Akramin; Akmeliawati, Rini (Institute of Electrical and Electronics Engineers Inc., 2016)
Tendon driven actuators are getting mature in electroactive polymer (EAP) researches. Research and development of the dielectric elastomer (DE) actuator from EAP family, have produced significant progress for decades. Dielectric elastomer is used in this paper to model a micro actuator platform. The parallel platform designing in this paper consists of the kinematics of the platform that is suited for micro structure of the robotic link. This may use for redundant manipulator or snake robot structure. DE is silicon artificial muscles that will actuated by applying voltage which perform a great actuation due to its linear large deflection. A remarkable amount of work has focused on delivering the feasibility of the robotic application of DE material. However, few commercial products equipped with polymer actuators have been introduced in the market, probably because most of the research has been dedicated either to discovering new actuation properties of the polymeric material. Therefore, this polymer is used to model the tendon driven parallel platform actuator for robotic application in this research. In this actuator design, both the upper and lower platforms are of configurations of equilateral triangles with DE cables attached close to the vertices. One DE cable attaches each of the vertices of the lower platform to the vertices directly above it on the upper platform. The three tendons thus enable the platform to exhibit 3 DOF. The dielectric polymer are attached with the three edges of the platforms that act like compression-tension cable because of their linear deformation characteristics. Therefore the platform of the DE actuator model is achieved in this research. This actuator can be used to develop redundant robot like snake robot or elephant trunk robot.